LINEAR PURSUIT–EVASION DIFFERENTIAL GAMES WITH JOINT CONTROL CONSTRAINTS - Yoldoshboyev Bakhromjon Ganijon ogli (THE HARMONY OF TRADITIONAL KNOWLEDGE AND MODERN INNOVATIONS, 2025)
Annotation:This paper studies linear pursuit–evasion differential games under joint control constraints that reflect shared limitations on players’ actions. Unlike classical models with independent controls, the admissible strategies are coupled through a common feasibility set. The analysis focuses on the impact of such constraints on equilibrium existence, strategy structure, and system trajectories. The results show that joint constraints significantly modify optimal behavior and introduce implicit coordination between antagonistic agents. The proposed framework is relevant for applications in robotics, security systems, and regulated economic environments where shared resources are present.